The Effectiveness of Using Mind Mapping in Improving English Writing Skills of the Tenth Grade Students of SMKN 1 Pujut - Pratiwi, Meilisa Cahya; Farmasari, Santi; Susanti, Ni Wayan Mira; Thohir, Lalu (Journal of English Education Forum (JEEF), 2025)
This research investigates the effectiveness of the Mind Mapping technique in improving the English writing skills of tenth-grade students at SMKN 1 Pujut. This study used a quantitative approach with a quasi-experimental design, involving two groups: an experimental class (X AP 1, 30 students) taught with Mind Mapping and a control class (X AP 3, 30 students) taught with conventional methods. Data were collected through pre-tests and post-tests of descriptive writing, and then scored based on content, organization, vocabulary, language use, and mechanics, and analyzed using SPSS with normality tests, homogeneity tests, and an Independent Samples t-test. The scores of the experimental group increased by 36.87 to 87.27 and the scores of the control group increased by 41.3 to 81.30 and statistical data confirmed that there was a significant difference (t = -5.207, p < 0.001). These findings showed that Mind Mapping was effective in terms of improving students in terms of organizing ideas, vocabulary and the quality of writing as a whole. One can conclude that Mind Mapping is a helpful teaching tool that encourages the development of creativity, logical thinking, and writing confidence, which makes it very helpful to both the teacher and the learner. Future studies could explore the long-term retention of writing skills acquired through Mind Mapping and investigate its effectiveness across different genres of writing and diverse learner populations.